Dechema chemistry data series : vapor liquid equilibrium data collection 2f organic hydroxy compounds, alcohols and phenols (supplement 4) - Gmehling, J.; Onken, U.; Rarey, J. R. (Frankfurt Dechema, 1990)
part 2f
Keywords: Vapor-Liquid equilibrium; Binary mixtures -- Data tables and diagrams; Organic hydroxy compounds